Effect of Covering of Head on Phototherapy Induced Hypocalecmia in Full Term Neonates with Jaundice (Medical Forum Monthly, 2024)
Objective: To see the effect of head covering on frequency of phototherapy induced hypocalcaemia in full term neonates with jaundice.Study Design: Case control study.Place and Duration of Study: This study was conducted at the Department of Pediatrics, Hayatabad Medical Complex, Peshawar from 01.07.2016 to 31.12.2016.Materials and Methods: In this study the total sample size was 128 patients using 13.88% preparation of hypocalcemia among neonates with lead covered during phototherapy 95% confidence interval and 6% margin of error. More over consecutive (Non probability) sampling technique was used for sample collection.Results: Our study show that in cases group mean age was 11 days with SD ± 3.27. Where as in control group mean age was 10 days with SD ± 2.93. In cases group 62% neonates were male, 38% neonates were female. Where as in control group 65% neonates were male, 35% neonates were female. In cases group 15% neonates had hypocalcaemia. Where as in control group 42% neonates had hypocalcaemia.Conclusion: Our study concludes that head covering on frequency of phototherapy induced hypocalcaemia is 15% in full term neonates with jaundice.